SEMIOSE E GRAMATICALIDADE - Vieira, Jorge de Albuquerque (Intercâmbio, 2010)
We will discuss here the concept of natural language as the result of a internalization process of actions between human systems and the environment. A homomorphy between these two levels carrying systemic coherence it’s the origem of natural languages and of the human communication systems.